Impulse blockade by intraocular tetrodotoxin during optic regeneration in goldfish: HRP-EM evidence that the formation of normal numbers of optic synapses and the elimination of exuberant optic fibers is activity independent - Hayes, WP (J Neurosci, 1989)
Optic fibers and synapses labeled with HRP were counted in the primary optic innervation layer of tectum after continuously blocking visual impulse activity with TTX during regeneration. Normal numbers of optic and nonoptic fibers and synapses were found at both 30 and 60 d, and key ultrastructural features of optic afferents such as fiber fasciculation, myelination, terminal clustering, synaptogenesis onto different classes of postsynaptic targets and general morphology were not notably affected by impulse blockade. These findings indicate that during regeneration the normal proliferation and elimination of optic fibers and the formation of normal numbers of optic synapses are not regulated by activity and are consistent with a pattern formation role for impulse activity rather than a trophic one.